2023
DOI: 10.1177/17455057231170061
|View full text |Cite
|
Sign up to set email alerts
|

Cancer burden in women with HIV on Medicaid: A nationwide analysis

Abstract: Background: Cancer is the leading cause of death in people living with HIV. In the United States, nearly 1 in 4 people living with HIV are women, more than half of whom rely on Medicaid for healthcare coverage. Objective: The objective of this study is to evaluate the cancer burden of women living with HIV on Medicaid. Design: We conducted a cross-sectional study of women 18–64 years of age enrolled in Medicaid during 2012, using data from Medicaid Analytic eXtract files. Methods: Using International Classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…First, our research findings examined the cervical cancer trends among women who were reported to be HIV-positive over time in one area of the United States. During a literature search on this topic, we found that many of the prior studies examined cervical cancer risk through clinical screening records [ 20 ]. We also found that many of these studies examined the cervical cancer risk in women who were reported to be HIV-positive and living outside the United States [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, our research findings examined the cervical cancer trends among women who were reported to be HIV-positive over time in one area of the United States. During a literature search on this topic, we found that many of the prior studies examined cervical cancer risk through clinical screening records [ 20 ]. We also found that many of these studies examined the cervical cancer risk in women who were reported to be HIV-positive and living outside the United States [ 21 ].…”
Section: Discussionmentioning
confidence: 99%